Obtaining the sGAG distribution profile in articular cartilage color images - Iglesias Comesaña, Carla; Luo, Lu; Martínez Torres, Javier; Taboada, Javier; Pérez, Ignacio (Biomedical Engineering / Biomedizinische Technik, 2020)
The articular cartilage tissue is an essential component of joints as it reduces the friction between the two bones. Its load-bearing properties depend mostly on proteoglycan distribution, which can be analyzed through the study of the presence of sulfated glycosaminoglycan (sGAG). Currently, sGAG distribution in articular cartilage is not completely known; it is calculated by means of laboratory tests that imply the inherent inaccuracy of a manual procedure. This paper presents an easy-to-use desktop software application for obtaining the sGAG distribution profile in tissue. This app uses color images of stained cartilage tissues taken under a microscope, so researchers at the Trinity Centre for Bioengineering (Dublin, Ireland) can understand the qualitative distribution of sGAG with depth in the studied tissues.
Keywords: articular cartilage; color image processing; glycosaminoglycan; proteoglycan; tissue; JCR; Scopus